Advanced Laser Technologies for Efficient Crystalline Silicon Solar Cells - Liu, Hao; Wang, Zilei; Tan, Zebin; Chen, Yonghui; Yang, Jie; Shen, Yibing; Lv, Mingzhi; Liu, Qiming; Xue, Chaowei; Fang, Liang; Xu, Xixiang; He, Deyan (Nano-Micro Letters, 2026)
Laser processing has emerged as a critical enabling technology in the manufacturing of high-efficiency crystalline silicon (c-Si) solar cells. This review systematically examines the fundamental principles and applications of laser technology within the photovoltaic industry. It begins by analyzing the critical influence of laser parameters on the laser–material interaction mechanisms, which ultimately determine the processing quality and the extent of thermal damage. A concise historical overview traces the evolution of laser applications from early laboratory research to later large-scale production of crystalline silicon solar cells. The core of the review is dedicated to a detailed discussion of specific application domains: the utilization of laser thermal effects for doping, oxidation, and crystallization; laser patterning for creating selective emitters, opening passivation layers, and defining intricate structures; and the revolutionary role of lasers in advanced metallization techniques, notably laser pattern transfer printing and laser-assisted sintering. Finally, the review outlines future development trends, highlighting the potential of ultrafast lasers, their integration with novel tandem cell concepts, and the rise of smart, multi-functional stations to push the efficiency and cost-effectiveness of c-Si solar cells. Highlights: 1 First holistic review: It provides the first systematic review encompassing the entire spectrum of laser processing techniques from doping and ablation to crystallization and contact optimization within the context of the complete high-efficiency c-Si solar cell manufacturing chain (passivated emitter and rear cell, tunnel-oxide-passivated contact, heterojunction, and back contact). 2 Enabler for next-generation cells: It critically highlights the role of laser processing as a key enabling technology for overcoming specific fabrication bottlenecks essential for the commercialization of next-generation cell architectures.